The benefits of Hospital Dentistry for the population: A scope review (Research, Society and Development, 2021)
Introduction: It is not clear all the benefits resulting from dental care in hospital environment. Objective: To map the evidence of the benefits of dentistry interventions in hospital settings for the population. Metodology: Literature scope review, using the databases Medline, Biblioteca Virtual de Saúde and Google Scholar, with the descriptors: Dental Care; Oral Health; Dental Staff; Hospital Dentistry Unit; Hospital. Inclusion criteria: interventions performed by the dental surgeon in a hospital environment; no period restriction. Languages: Portuguese, English and Spanish. Endnote Web was used for reference manipulation. Results: The search identified 4349 abstracts of articles, and 111 were selected in the screening. Forty-eight texts were read, resulting in 11 studies. The studies were conducted with patients of various age groups and/or with different diseases and conditions. The benefits were: prevention of pneumonia, infectious foci, osteoradionecrosis, myocardial infarction; reduction of oral mucositis in cancer treatment, with improved quality of life; reduced hospitalization and hospital costs. Conclusion: The benefits that the dentist brings to the population in the hospital environment and to the health establishment are valuable, and their presence in this place should be stimulated.